Meeting the data challenge in education: a knowledge and innovation exchange - Crouch, Luis (Global Partnership for Education, 2019)
The purpose of this paper is to describe the current landscape in education data systems and spark discussion and debate around potential areas for KIX investment.
EdTechHub.ItemAlsoKnownAs: 2339240:PYIIMTJL;2339240:PYIIMTJL Old URL: https://www.globalpartnership.org/content/meeting-data-challenge-education-knowledge-and-innovation-exchange-kix-discussion-paper
Keywords: ___working_potential_duplicate